Need Analysis of Pharmacy Students in Toefl Preparation Class - Astri, Zul; Nur, Sahril; Misnawati, Misnawati (Universitas Hamzanwadi, 2022)
In response to the demand for higher education institutions to internationalize their campuses and strengthen their students' global collaboration, Sekolah Tinggi Ilmu Farmasi (STIFA) Makassar has made English language proficiency a requirement for graduation. The evidence is bypassing the TOEFL test held by universities. This study aims to analyze the students' learning styles and expectations for studying English in TOEFL class and the students' difficulties. This study was conducted at one of the Pharmacy campuses in Central Indonesia, Makassar, South of Sulawesi, namely the Sekolah Tinggi Ilmu Farmasi (STIFA) Makassar with 62 people as a population. While using purposive sampling, there were 20 people chosen as a sample. From this research, we found that 60% of students prefer the auditory learning style and 100% of students expect the teacher to teach combined in English and Indonesian, gives many exercises, and provides new vocabulary in every meeting. In addition, 65 % of students select Structure and Written Expression as the most challenging skill in TOEFL class.